Analysis of Inner Structure and Physical Structure of the Poetry “Love’s Philosophy” by Percy Bysshe Shelley - Wati, Lisna; Pertala, Erik Candra; Hestiana, Siska (Apollo Project: Jurnal Ilmiah Program Studi Sastra Inggris, 2023)
The title of this study is an analysis of the Inner Structure and Physical Structure of Percy Bysshe Shelley's Love's Philosophy poetry. This study aims to formulate the inner structure and physical structure in the Love's Philosophy by Percy Bysshe Shelley. This study uses a descriptive-qualitative research method with a read-note analysis technique. This data analysis is obtained by carrying out several stages: reading, taking notes, and analyzing each line and stanza that belongs to the inner structure and physical structure. Based on the results of the analysis of “Love's Philosophy” poetry by Percy Bysshe Shelley, it has an inner structure in the form of theme, feeling, tone and message. The physical structure that is owned is in the form of diction, images or imagery, concrete words, figurative language , rhyme, and typography. Keywords: Poetry, Structure, Inner, Physical